1995
DOI: 10.1007/bf00133616
|View full text |Cite
|
Sign up to set email alerts
|

Effects of suramin on metastatic ability, proliferation, and production of urokinase-type plasminogen activator and plasminogen activator inhibitor type 2 in human renal cell carcinoma cell line SN12C-PM6

Abstract: Effects of suramin, a polysulfonated naphthylurea compound, on metastatic ability, proliferation, and production of plasminogen activators and plasminogen activator inhibitors were studied using the highly metastatic human renal cell carcinoma cell line, SN12C-PM6. After renal subscapular implantation of tumor cells in nude mice, suramin significantly inhibited metastasis of tumor cells to the lungs and liver. In vitro growth of tumour cells was inhibited by suramin in a dose-dependent manner, at relatively lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…In addition, NF-kB signal blockade does not affect tumor cell proliferation in vitro or in vivo but prevents intravasation of tumor cells in an in vivo chick chorioallantoic membrane model of metastasis as well as spontaneous metastasis in a murine model. In SN12C-PM6, Marutsuka et al [35] have reported that the increase in plasminogen activator inhibitor 2 and the decrease in urokinase-like plasminogen activator correlate with the inhibitory effects on tumor growth and metastasis by suramin. In other type of tumor, UCH-L1 protein expression is lower in the primary tumor cell line than in the nontumor cell line of melanoma and breast cancer [30,31].…”
Section: Ubiquitin Carboxyl-terminal Hydrolase Isozyme L1 (Uch-l1 Pgmentioning
confidence: 97%
“…In addition, NF-kB signal blockade does not affect tumor cell proliferation in vitro or in vivo but prevents intravasation of tumor cells in an in vivo chick chorioallantoic membrane model of metastasis as well as spontaneous metastasis in a murine model. In SN12C-PM6, Marutsuka et al [35] have reported that the increase in plasminogen activator inhibitor 2 and the decrease in urokinase-like plasminogen activator correlate with the inhibitory effects on tumor growth and metastasis by suramin. In other type of tumor, UCH-L1 protein expression is lower in the primary tumor cell line than in the nontumor cell line of melanoma and breast cancer [30,31].…”
Section: Ubiquitin Carboxyl-terminal Hydrolase Isozyme L1 (Uch-l1 Pgmentioning
confidence: 97%
“…Given the poor prognosis of pancreatic cancer patients it is not surprising that there was increased expression of uPA and uPAR in fresh pancreatic cancer tissue and that over expression was related with poorer survival [29]. That uPA and its receptor uPAR can act as a target for anti-cancer therapy has been extensively documented in mouse models [30,31]. Bound to its specific cell surface receptor (uPAR), uPA efficiently converts the inactive zymogen, plasminogen, into the active serine protease, plasmin, which then cleaves either directly or indirectly extracellular matrix components including laminin, fibronectin, and collagen [26,27].…”
Section: Targeting Vectorsmentioning
confidence: 99%
“…More recently its wider potential has been investigated (Voogd et al, 1993) and it has undergone trials as an anti-cancer agent in possible treatment of metastatic cancers such as hormone refractory prostate cancer (Rago et al, 1991;Miglietta et al, 1992) and adrenocortical carcinomas (Stein et al, 1989). The ability of suramin tc inhibit cancer metastasis (Marutsuka et al, 1995) may have implications in other conditions where matrix degradation occurs. Several mechanisms of action have been proposed including inhibition of angiogenesis (Gagliardi et al, 1992) and inhibition of proteinases (Cad6ne et al, 1997).…”
Section: Introductionmentioning
confidence: 97%